Getting Digital Assets from Public–Private Partnership Research Projects through “The Valley of Death,” and Making Them Sustainable - Aartsen, Wendy; Peeters, Paul; Wagers, Scott; Williams-Jones, Bryn (Frontiers in Medicine, 2018)
Projects in public-private partnerships, such as the Innovative Medicines Initiative, produce data services and platforms (digital assets) to help support the use of medical research data and IT tools. Maintaining this assets beyond the funding period of a project can be a challenge. The reason for that is the need to develop a business model that integrates the perspectives of all different stakeholders involved in the project and these digital assets might not necessarily be addressing a problem for which there is an addressable market of paying customers. In this manuscript, we review 4 IMI projects and the digital assets they produced as a means of illustrating the challenges in making digital assets sustainable and the lessons learned. To progress digital assets beyond proof-of-concept into widely adopted tools, there is a need for continuation of multi-stakeholder support tailored to these assets. This would be best done by implementing a structure similar to the accelerators that are in place to help transform startup businesses into growing and thriving businesses. The aim of this article is to highlight the risk of digital asset loss and to provoke discussion on the concept of developing an ‘accelerator’ for digital assets from public-private partnership research projects to increase the chance that digital assets will be sustained and continue to add value long after a project has ended.